COMPONENT ANALYSIS OF ANTHROPOMETRIC VARIABLES OF BOYS AGES 7-9 WHICH ARE CLASSIFIED BY AGE GROUPS - Alija Biberović,; Muris Đug,; Tarik Huremović, (Sport Scientific And Practical Aspects, 2025)
Following of growth, functional and psychomotor capabilities of pupils enables better perceiving of influences of certain living conditions as well as success of teaching process and measures that need to be taken to have better development. The main goal of this work comes from research project called “Static and explosive strength of 7-9 year old boys in relation to the proportionality of body structure”. The goal of this research is establishment of significant main components of anthropometric variables of 7-9 year old boys classified by age groups (+- 6 months). Structure in the area of anthropometric variables of boys aged 7-9 was analysed by using a sample of 286 boys by using a Hotelling component analysis.